Review on the Eyedrop Self-Instillation Techniques and Factors Affecting These Techniques in Glaucoma Patients - Ozcan Kayikcioglu; Sinan Bilgin; Murat Uyar (Scientifica)
Objective. This study aims to evaluate eyedrop self-installation techniques and factors affecting these techniques in glaucoma patients. Methods. Researchers directly observed eyedrop instillation procedures of 66 glaucoma patients. Contact with periocular tissues and instillation onto ocular surface or conjunctival fornices were considered. Correlations of instillation patterns with patient characteristics including age, gender, intraocular pressure, cup-to-disc ratio, visual field loss, and total intake of glaucoma medication and handgrip strength score were searched. Results. The average handgrip strength in the instillation without periocular contact group was 66.4 ± 19.7 kg, while the average handgrip strength score was 55.9 ± 20.9 kg in the instillation with contact group. The difference between the two groups was statistically significant (p=0.039). No statistically significant correlation was found between handgrip strength and the mean number of glaucoma medications, c/d, intraocular pressure (p>0.05). Also there was no significant relation between mean handgrip strength score and the severity of the visual field defect (p=0.191). Conclusion. Patients especially with severe glaucomatous damage should be adequately instructed about the proper techniques for self-instillation of eyedrops and motivated to use a proper technique. Also, it is possible to suggest that patients with a higher handgrip strength, indicating the well-being of general health, may be doing better in properly instilling glaucoma eyedrops.